Clinical experience with recombinant prourokinase for complex retinal diseases in type 2 diabetes - L.K. Moshetova; Yu.B. Slonimsky; I.V. Vorobyeva; A. Dgebuadze; O.V. Agafonova; E.P. Delver; A.A. Belogurov (РМЖ "Клиническая офтальмология")
Background: medical treatment of vitreous and retinal hemorrhages is a relevant issue. Considering this, the authors review published data of different years. Fibrinolytic enzymes are reasonable for vitreous and retina hemorrhages treatment from the viewpoint of pathogenesis.  Aim: to improve treatment strategies for complex retinal diseases (i.e., diabetic retinopathy, hypertensive retinopathy, “wet” age-related macular degeneration (AMD) with hemorrhages in type 2 diabetes) using recombinant prourokinase by dynamic retinal changes and tear levels of vascular endothelial growth factor (VEGF-A).  Patients and Methods: 30 patients (30 eyes) with diabetic retinopathy, hypertensive retinopathy, and AMD were examined. All patients were subdivided into 4 groups. Best-corrected visual acuity (BCVA), retinal light sensitivity (using MAIA microperimetry), vitreous hemorrhage severity (using vitreous hemorrhage density grading scale), intraocular pressure, and tear levels of VEGF-A (by ELISA) were measured.  Results: after treatment with recombinant prourokinase, VEGF-A level was 1520–1640 pg/mL. Ocular parameters (i.e., BCVA, retinal light sensitivity, and vitreous hemorrhage severity) and eye fundus manifestations are likely to benefit from recombinant prourokinase. It was demonstrated that recombinant prourokinase is highly effective for vitreous and retinal hemorrhages in patients with complex retinal diseases.  Conclusion: fibrinolytic treatment provided stabilization of pathological process in patients with complex retinal diseases since VEGF-A tear levels did not change significantly. The result of standard treatment was significant increase in VEGF-A levels thus demonstrating the activity of pathological process despite the treatment. Single intravitreal injection of recombinant prourokinase (0.2 mL, 500 IU) on day 3 after the disease begins and further daily parabulbar injections of recombinant prourokinase (5000 IU/0.5 mL of sodium chloride 0.9%) of 10 injections are recommended for complex retinal diseases (i.e., vitreous, retinal hemorrhages) in type 2 diabetes.  Keywords: diabetic retinopathy, hypertensive retinopathy, age-related macular degeneration, vascular endothelial growth factor, fibrinolytic, fibrinolytic treatment, recombinant prourokinase, Gemase.  For citation: Moshetova L.K., Slonimsky Yu.B., Vorobyeva I.V. et al. Clinical experience with recombinant prourokinase for complex retinal diseases in type 2 diabetes. Russian Journal of Clinical Ophthalmology. 2019;19(2):73–79. About the authors: 1Larisa K. Moshetova — MD, PhD, Professor, Academician of the Russian Academy of Sciences, Head of Ophthalmology Department, ORCID iD 0000-0002-5899-2714; 1Yury B. Slonimsky — MD, PhD, Professor of the Department of Ophthalmology, ORCID iD 0000-0002-5656-4919; 1Irina V. Vorobyeva — MD, PhD, Associate Professor of the Department of Ophthalmology, ORCID iD 0000-0003-2707-8417; 1Ana Dgebuadze — postgraduate student of the Department  of Ophthalmology, ORCID iD 0000-0002-9518-0459; 2Olga V. Agafonova — PhD in Biology, Research Scientist, ORCID iD 0000-0002-7483-7167; 2Evgeny P. Delver — PhD in Biology, Senior Research Scientist, ORCID iD 0000-0003-2319-7937; 2Anatoly A. Belogurov — PhD in Biology, Leading Research Scientist, ORCID iD 0000-0002-7170-9530. 1Russian Medical Academy of Continuous Professional Education. 2/1, Barrikadnaya str., Moscow, 125993, Russian  Federation. 2Research Institute of experimental cardiology of the National Medical Research Center of Cardiology. 15а, 3rd Cherepkovskaya str., Moscow, 121552, Russian Federation. Contact information: Irina V. Vorobyeva, e-mail: irina.docent2000@mail.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 15.04.2019.